A Study on Efficiency of Capital Structure”: Evidence from Bajaj Auto Limited - Nayak, Vinay D (International Journal of Psychosocial Rehabilitation, 2020)
Capital structure is that structure at the level of debt and equity proportion where the market value per share is maximum and the cost of capital is minimum. Planning the capital structure is one of the most difficult areas of financial decision making because of the inter-relationship among components of the capital structure and its connected to risk-return value of the enterprise. Business enterprise depends either debt or equity for their sources of fund but, rational decision only will help them to undergo the seasonable choice to select a capital structure in long run. Otherwise the debt burden and fiscal difficulties will trouble the organization. Since automobile industry is a core industry it needs huge investment for their working capital and related fund requirements. Therefore, the researcher made an attempt to analyze the financial performance and automobile based on their capital structure. Study conducted based on secondary data for the period of five years from 2015- 2019 to interpret the financial position of the company.